L2 stable transparency optimized two channel teleoperation under time delay - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper presents a novel two channel control law for high transparency teleoperation under time delay with guaranteed delay independent L2 stability. Four channel controllers have long been known to provide transparent teleoperation when time delay does not exist on the communication channels. However under time delay, a trade-off between delay and transparency must be made to make the system stable. Previously, four channel controllers with damping injection have been proposed to realize this trade-off. However, when using four channels the compromise in transparency is not ideal. In this paper, by introducing a two channel control architecture with damping injection and force reflection filters we realize an L2 stable teleoperation system with better transparency/performance compared to the four channel teleoperation systems under time delay. The validity of our approach is confirmed theoretically and by experiments. © 2015 IEEE.